Analysis of the properties of biodiesel from avocado pulp as a lubricant: pin on disk test (Research, Society and Development, 2020)
This work has a multidisciplinary principle and addresses different areas, such as mechanical engineering, chemistry and biology. The objective is to demonstrate the characteristics of avocado biodiesel as a biolubricant for applications in diesel cycle engines. The methodology used begins with the extraction of oil from the avocado pulp, the process of which was carried out using the chemical solvent extraction technique. Afterwards, the process of transesterification of avocado oil was carried out to obtain biodiesel. Next, the avocado pulp biodiesel was used in the tribological test and the residue was analyzed in the X-ray spectrometer. Understanding the characteristics of avocado biodiesel as a biolubricant makes it possible to understand characteristics of friction, and with that, it is possible to reduce component failures. The result of this work shows that avocado biodiesel can be used as a biolubricant and has  wear properties in the combustion engine similar to that of mineral diesel.